Analyzing the environmental ideas of knowledgeable citizens toward the realization of a creative city in Tabriz - Heydar Beheshti Asl; Morteza Mirgholami; Karim Hosseinzadeh Dalir (آلودگی‌های محیطی و توسعه پایدار شهری)
The realization of a creative city necessitates the systematic integration of social, cultural, and environmental innovation. This study, focusing on the metropolis of Tabriz, analyzes the ideas of knowledgeable citizens to explain the role of the environment as a key component in the creative city model. Out of 2,254 ideas collected through participatory calls, environment-related submissions were categorized and evaluated into 14 semantic clusters. These included themes such as water resource management, education, ecosystem regeneration, ecological design, pollution control, and the green economy. The findings indicate that, although these ideas ranked in the mid-range in terms of numerical frequency, they received the highest average scores on indicators such as innovation, long-term sustainability, alignment with upstream documents, and scientific grounding. Final discourse analysis revealed that the citizens of Tabriz regard the environment not merely as a technical concern but as a foundation for urban creativity, collective participation, spatial justice, and the regeneration of ecological identity. Based on this analysis, a conceptual model of the environmental-creative city of Tabriz was developed. This model integrates the three domains of citizen discourse, institutional innovation, and ecological infrastructure within a unified framework aimed at realizing a sustainable and creative urban ecosystem. Finally, recommendations are offered for leveraging public capacities in urban policymaking.